Moderating and mediating mechanisms of the association between endogenous testosterone and aggression in youth: A study protocol - Esther Calvete; Nerea Cortazar; Izaskun Orue (PLoS ONE, 2025)
Background The role of testosterone, particularly in combination with cortisol, in aggression remains debated. According to the general aggression model, hormones interact with other variables, such individuals’ knowledge structures, to predict aggression. This model may help explain inconsistent findings of previous research. Furthermore, the model posits that the influence of hormones on aggressive behavior is mediated by the individual’s internal state. Accordingly, the objectives of this study are to assess whether (1) testosterone and cortisol, alone and in interaction with aggression-related knowledge structures, predict aggression in a standardized laboratory paradigm and whether (2) this association is mediated by hostile attribution, anger, and arousal. By identifying key moderators and mediators, this study seeks to make a very novel contribution to the understanding of the role of testosterone in aggressive behavior. These objectives will also be assessed separately for males and females. Methods The Point Subtraction Aggression Paradigm will be used to assess aggression. The sample will include 110 youths aged 17–19 (50% male). Participants will provide saliva samples before and after completing the paradigm, along with measures of three aggression-related knowledge structures (justification of violence, hostility, and narcissism) collected before the paradigm. Measures of two mediators (hostile attribution, anger) will be obtained after completing the paradigm. Arousal levels (heart rate and skin conductance) will be recorded before, after, and while completing the paradigm. The hypotheses will be tested using path analysis models, examining both the testosterone/cortisol ratio and the interaction between testosterone and cortisol as well as both baseline hormone levels and changes in hormone levels. Discussion Although it may be limited by the use of saliva for measuring hormones, this study will enhance the current understanding of the role of testosterone and cortisol in aggressive behavior among youths by investigating novel hypotheses related to psychological moderating and mediating factors.